Evaluation of Vancomycin Dosing in Patients With Cirrhosis: Beginning De-Liver-ations about a New Nomogram. (April 2019) - Regal, Randolph E.; Ren, Steven P.; Paige, Gregory; Alaniz, Cesar
Background: Reduced hepatic production of creatinine precursors in patients with decompensated cirrhosis leads to falsely low serum creatinine values. Therefore, when performing empiric dosing of vancomycin, an overestimation of creatinine clearance may result in significantly supratherapeutic vancomycin levels and increased risks of nephrotoxicity.Objective: The objective of the study is to evaluate vancomycin dosing requirements in patients with cirrhosis stratified by Child-Pugh Score, with subsequent comparison with doses that are recommended in the previously published and validated Kullar nomogram.Methods: A retrospective evaluation of patients with cirrhosis who received vancomycin for at least 3 full days and had at least 1 serum concentration drawn. Vancomycin daily dose and corresponding serum concentration were collected with patients stratified by Child-Pugh Score for comparison. Each patient had their vancomycin dose compared with the dose suggested by a published nomogram.Results: A total of 201 courses of vancomycin were followed. There were no significant differences between the Child-Pugh cohorts with respect to initial vancomycin dosing. There was also no significant difference in the median initial vancomycin trough concentration between the 3 cohorts (Child-Pugh A: 13.7 µg/mL [interquartile range, IQR: 10.4-22.1]; Child-Pugh B: 20.2 µg/mL [IQR: 15.1-25.9]; Child-Pugh C: 19.3 µg/mL [IQR: 14.9-25.2, P = .08]. The median vancomycin dose using the Kullar nomogram would have been 3.0 g/day (IQR: 2.0-3.75, P < .001), but the median dose actually used in this patient population was significantly less at 2.0 g/day. Nonetheless, the median vancomycin trough concentration in the entire patient population was 19.8 µg/mL (IQR: 15.4-25.9).Conclusion: In patients with cirrhosis, there was a high incidence of supratherapeutic vancomycin serum concentrations despite the fact that dosing was significantly less than that suggested by the published Kullar nomogram.